The repetition principle of traumatic dreams - Avcı, Mahsum (Scientific reports, 2025)
The purpose of the present study was to determine the recurrent traumatic dreams of university students and to examine their dreams based on a psychodynamic viewpoint. The study group of this research, which is based on qualitative research design, was determined using the criterion sampling method, which is one of the purposive sampling methods. In this way, 64 people who met the following criteria were reached and a total of 130 repeated dreams were obtained. After the thematic analysis of the dreams, four main themes and four sub-themes were identified: (1) The Threat Theme, (2) The Theme of Dissociation and Somatic Response, (3) The Theme of Abandonment Depression and Self-Activation, and (4) The Theme of Forced Birth. The study not only categorizesf recurrent traumatic dreams and reveals the type of these dreams, but also emphasizes the importance of psychic functioning in the context of the psychodynamic perspective. In this respect, it is considered that talking about the repetitive traumatic dreams of individuals who apply for psychological counseling and analyzing such dreams will contribute to a more detailed study of the subject brought to counseling sessions.